The Belle of Bedford Avenue : The Sensational Brooks-Burns Murder in Turn-of-the-Century New York - McConnell, Virginia A., 1942- (True crime history series., 2019)
At the turn of the 20th century, many affluent Brooklyn teens and young adults were bucking the constraints of their immigrant parents and behaving badly: drinking, having sex, staying out all night, stealing, scamming local businesses, and engaging in other more serious activities. When 20-year-old Walter Brooks was murdered in a seedy Manhattan hotel in 1902, the ensuing court case was front-page news throughout the country. The hearings featured testimonies about these young people's secret lives that shocked parents and inspired much editorial commentary in the newspapers. From start to finish, the case was viewed as a cautionary tale for parents, for boys who could be led astray, and for girls who risked their reputations to be popular. Set against the colorful backdrop of Coney Island, roadhouses, forbidden dance halls, and vaudeville, The Belle of Bedford Avenue follows the young woman at the heart of the case from her trial for the murder of Walter Brooks to her adulthood. The crime itself, interestingly, occurred in the location of Ground Zero and today's September 11 Memorial. The trial was conducted by William Travers Jerome, who went on to become a legendary New York City prosecutor.